An Usul Al-Fiqh Analysis of Underage Unregistered Marriage in Indonesia: a Sadd Al-Dhari’ah Approach to Preventing Social Harm - Nasiri Nasiri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
Underage unregistered marriage, locally known as nikah siri, remains a persistent socio-legal challenge in Indonesia despite the enactment of Law No. 16 of 2019, which raised the minimum marriageable age. This practice often bypasses state administration, creating a legal vacuum that marginalizes women and children. This research aims to analyze the legal status and consequences of such unions through the lens of Usul al-Fiqh, specifically utilizing the doctrine of Sadd al-Dhari’ah (the obstruction of means). Employing a qualitative normative-juridical methodology, this study evaluates primary Islamic legal texts alongside Indonesian marriage regulations and empirical social data. The findings reveal that while these marriages may satisfy the formal pillars of a religious contract, they constitute a "means" (wasilah) that leads to definitive social and legal harm (mafsadah), including the loss of civil identity, reproductive health risks, and economic vulnerability. The study concludes that applying Sadd al-Dhari’ah provides a robust theological justification for prohibiting underage unregistered marriage, as it prioritizes public interest (maslahah al-ammah) and the preservation of lineage (hifdz al-nasl) over the narrow private benefit of moral prevention. This approach offers a framework for Indonesian policymakers and religious authorities to harmonize religious ethics with modern child protection standards.